Manajemen risiko perbankan syariah - wahyudi, wandi wahyudi (Maliki Interdisciplinary Journal, 2026)
Islamic banks are financial institutions that operate based on Islamic law. In their operations, Islamic banks are exposed to various risks that may affect their stability and business sustainability. Therefore, the implementation of risk management is highly crucial. This study aims to examine the concept of risk management and identify the various types of risks faced by Islamic banking. The method used is a literature study by reviewing various scientific sources such as books, journals, and official reports. The results of the study show that risk management is carried out through several stages, namely risk identification, measurement, monitoring, and control. Proper implementation of risk management can reduce potential losses while increasing public trust in Islamic banks.